Digital marketing strategy for TMC - Sanvictores, Maribeth C.; Cruz, Edison D. (Quezon City University of the Philippines Diliman, 2011)
The digital world has emerged as the result of today's rapid technology advancement. The way people live has changed - the way we communicate, the way we connect with each other, the way we gather information and the way we buy the things we want and need. In turn, digital marketing has also changed the way businesses promote its products and services through the use of different channels such as websites, mobile phones SMS/MMS, display/banner ads and digital outdoor, podcast, voice broadcast, etc. One of the digital channels that have become the faster bridge in doing business and providing services to customers innovatively is the Internet. This in turn paves a new and cheaper way to market in reaching the target customers through implementing internet marketing strategies.

The Technology Management Center of the University of the Philippines-Diliman (UP-TMC) is the first of its kind in the country that offers the course Master of Technology Management (MTM). Since its name can easily be mistaken for a technical graduate program rather than a business graduate course, potential enrollees opt to enroll in Master of Business Administration instead. In fact, the result of the survey conducted on non-MTM students shows that only 35 percent answered Yes on the question if they are familiar with the MTM program of UP-TMC and 65 percent answered No. Also, there was a decline in the applications for the MTM program at UP-TMC on the school year 2010-2011 but there was no data on the reasons behind this decline. MBA and the top schools who offer this program are considered as the UP-TMC's competitors based on the enrollment data for the school years 2007-2008 to 2009-2010.

There are around six billion internet users in the world and around 29 million users in the country and internet search emerges as the top online activity. Social Networking Websites are becoming popular among these internet users in connecting and communicating with each other. In the result of the survey on 44 MTM students and 34 Non-MTM students, it shows that 97 pecent of them have accounts on social networking websites and 92 percent has Facebook account, while Email is the top online activity of the respondents.

Thus, this paper aims to build awareness and interest about TMC and the MTM program through the use of the digital internet by formulating internet marketing strategies for TMC. The internet marketing strategies specifically aim to increase the web traffic of TMC website, foster professional networks among its students and alumni, promote the discipline of technology management to the industry and the public, and reach the international market. In addition, the online strategic goals recommended in this study include : 1) improve website design, 2) Enhance features and functionality, 3) Foster online community and 4) Build interest of the international market.

The Internet Marketing Strategies formulated include 1) Website Strategy in terms of Visual design/Presentation and layout, Content and Features; and 2) Search Engine Optimization; and 3) Digital Communications Strategy which include Social Media Marketing, Email Marketing, Blog Marketing and Webinar.

How to evaluate the marketing program is recommended in order to determine the effectiveness of the internet marketing strategies. Recommendations include commitment of the UP-TMC in implementing the internet marketing strategies, acquiring services of an internet marketing consultant for the first six months of the implementation, internet marketing strategies be coupled with traditional marketing such as Public Relations, and exploring the use of other digital channel such as mobile MMS/SMS and e-learning opportunity to serve the international market.

A survey was conducted on 44 MTM students and 34 non-MTM students to determine their online activities, the factors influencing them in choosing a masteral degree, and the website features that will make them visit a website regularly. UP-TMC Executive Director Edison Cruz was interviewed and the interview video series from Ms. Janette Toral, a well-known internet marketing expert in the Philippines was used as reference for the development of internet marketing strategies in this study. Moreover, the marketing strategy was guided by the Internet Marketing by Rafi a. Mohammed Robert J. Fisher, Bernard J. Jaworski, Gordon J. Paddison and certain steps and frameworks were used. Finally, PEST analysis, internet-specific SWOT analysis, online competitive analysis, and analysis of current digital capabilities of UP-TMC were conducted

This paper is an attempt to develop a digital marketing strategy for an academic institution like UP-TMC. Hence, certain limitations are unavoidable such as on the data gathered specifically there were only seven alumni who took the survye, there was no data gathered regarding the student applications from other academic institutions, and relied on online search in determining the online activities of other universities in the Philippines. A future study that will explore digital marketing strategies using other digital channels such as Mobile phones SMS/MMS and provide e-learning courses to serve the international market is recommended.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Electronic commerce; Internet marketing